Application of Microgranule from IAA Producing-Endophytic Bacterial as Biofetilizer on Rubber Plants (Hevea brasiliences Muell. Arg.) - Ardiansyah, Agung; Warsito, Kabul; Ginting, Tri Yanita (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2023)
Rubber plant (Hevea brasiliensis Muell.Arg) is the main commodity of plantations, some of whose products are exported and some to meet domestic needs as raw materials for industrial purposes. Purpose on research diversity and crateristics of endophytic bacteria producing hormone IAA from rubber plants. Then the effectiveness treatment of microgranules addition and immersion of endophite bacterial suspension and rubber seed soaking suspension to spur the growth of rubber plants. This research was conducted using the factorial CRD (Completely Randomized Design) method consisting of 16 treatments with 2 replications. The first factor was immersion of endophite bacterial suspension consisting of R0 = 0 hours; R1 = 12 hours; R2 = 24 hours and R3 = 36 hours and the second factor was the addition of microgranules consisting of J0 = 0 gr; J1 = 10 gr; J2 = 15 gr; J3 = 20 gr. The results of this study showed that the results on the isolation of endophite bacteria from the tea plant from the roots and stems of the tea plant yielded 3 isolates from plant roots and 2 isolates from plant stems. For IAA levels, the five isolates were positive. The use of endophytic bacteria as an alternative biofertilizer has a significant effect on the parameters observed